Understanding the roles of the thylakoid lumen in photosynthesis regulation - Järvi, Sari; Gollan, Peter J.; Aro, Eva-Mari (Frontiers in Plant Science, 2013)
It has been known for a long time that the thylakoid lumen provides the environment for oxygen evolution, plastocyanin-mediated electron transfer and photoprotection. More recently lumenal proteins have been revealed to play roles in numerous processes, most often linked with regulating thylakoid biogenesis and the activity and turnover of photosynthetic protein complexes, especially the PSII and NAD(P)H dehydrogenase-like complexes. Still, the functions of the majority of lumenal proteins in Arabidopsis thaliana are unknown. Interestingly, while the thylakoid lumen proteome of at least 80 proteins contains several large protein families, individual members of many protein families have highly divergent roles. This is indicative of evolutionary pressure leading to neofunctionalisation of lumenal proteins, emphasizing the important role of thylakoid lumen for photosynthetic electron transfer and ultimately for the plant fitness. Furthermore, the involvement of anterograde and retrograde signaling networks that regulate the expression and activity of lumen proteins is increasingly pertinent. Recent studies have also highlighted the importance of thiol/disulphide modulation in controlling the functions of many lumenal proteins and photosynthetic regulation pathways.